High performance all-organic flexural piezo-FET and nanogenerator via nanoscale soft-interface strain modulation - Dhakras, Dipti; Gawli, Yogesh; Chhatre, Shraddha; Wadgaonkar, Prakash; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Flexural strain fields are encountered in a wide variety of situations and invite novel device designs for their effective use in sensing, actuating, as well as energy harvesting (nanogenerator) applications. In this work we demonstrate an interesting all-organic device design comprising an electrospun P(VDF-TrFE) fiber-mat built directly on a conducting PANI film, which is also grown on a flexible PET substrate, for flexural piezo-FET and nanogenerator applications. Orders of magnitude stronger modulation of electrical transport in PANI film is realized in this device as compared to the case of a similar device but with a uniform spin-coated P(VDF-TrFE) film. We find that in the flexural mode of operation, the interaction between the laterally modulated nanoscale strain field distributions created by the fibers and the applied coherent strain field strongly influences the carrier transport in PANI. The transport modulation is suggested to occur due to strain-induced conformational changes in P(VDF-TrFE) leading to changes in carrier localization-delocalization. We further show that the fiber-mat based device system also works as an efficient nanogenerator capable of delivering power for low power applications.

Hexaphosphate-derived phosphorus-functionalized carbon for lithium-ion battery anode - Gawli, Yogesh; Wahid, Malik; Fernandez, Rohan; Kothari, Dushyant; Shelke, Manjusha; Ogale, Satishchandra B. (Chemistryselect, 2017)
We show that high-temperature annealing of a dried hexaphosphate, namely phytic acid, renders activated (micro-porous) and phosphorus-functionalized graphene like carbon in a one-step process. At high enough temperature few volatile phosphates serve as porogen-forming entities while other groups reactively functionalize the carbon surface. The optimized material has high effective surface area due to the presence of defect states. As an anode material for Li-ion battery, it exhibits a reversible capacity that is double that of the graphite and is stable for 1000 cycles even at a high current of 5 A g(-1). This result is attributed to the concurrent presence of micropores and phosphorus containing groups in the carbon matrix.

High and reversible lithium ion storage in self-exfoliated triazole-triformyl phloroglucinol-basedcovalent organic nanosheets - Haldar, Sattwick; Roy, Kingshuk; Nandi, Shyamapada; Chakraborty, Debanjan; Puthusseri, Dhanya; Gawli, Yogesh; Ogale, Satishchandra; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2018)
Covalent organic framework (COF) can grow into self-exfoliated nanosheets. Their graphene/graphite resembling microtexture and nanostructure suits electrochemical applications. Here, covalent organic nanosheets (CON) with nanopores lined with triazole and phloroglucinol units, neither of which binds lithium strongly, and its potential as an anode in Li-ion battery are presented. Their fibrous texture enables facile amalgamation as a coin-cell anode, which exhibits exceptionally high specific capacity of approximate to 720 mA h g(-1) (@100 mA g(-1)). Its capacity is retained even after 1000 cycles. Increasing the current density from 100 mA g(-1) to 1 A g(-1) causes the specific capacity to drop only by 20%, which is the lowest among all high-performing anodic COFs. The majority of the lithium insertion follows an ultrafast diffusion-controlled intercalation (diffusion coefficient, D-Li(+) = 5.48 x 10(-11) cm(2) s(-1)). The absence of strong Li-framework bonds in the density functional theory (DFT) optimized structure supports this reversible intercalation. The discrete monomer of the CON shows a specific capacity of only 140 mA h g(-1) @50 mA g(-1) and no sign of lithium intercalation reveals the crucial role played by the polymeric structure of the CON in this intercalation-assisted conductivity. The potentials mapped using DFT suggest a substantial electronic driving-force for the lithium intercalation. The findings underscore the potential of the designer CON as anode material for Li-ion batteries.